2015
DOI: 10.1080/02640414.2014.996183
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary predictors of adherence to contemporary dance training: findings from the UK Centres for Advanced Training

Abstract: Little is known about the predictors of adherence in a dance context. The aim of this study was to investigate adherence to a dance talent programme using a multidisciplinary set of variables representing psychological correlates of adherence, maturation and physical factors relating to dance talent. Psychological (passion, motivational climate perceptions, eating attitudes), physical competence (vertical jump height, handgrip strength, hamstring flexibility, external hip rotation, aerobic fitness), and matura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…The dancers’ ability to negotiate these transitions successfully appeared to rely on their motivation and psychological characteristics and skills ( Abbott and Collins, 2004 ; Stambulova et al, 2009 ), and, due to the exploratory and inductive nature of the research, additional factors such as social support, experience, and work-life balance. These findings provide support for a number of previous studies in areas including motivation (e.g., Aujla et al, 2014 , 2015 ), mental skills (e.g., Vealey, 2007 ) and PCDEs ( MacNamara et al, 2010a , b , 2008 ; MacNamara and Collins, 2011 ), and represent the first time that such factors have been investigated simultaneously in dance. The key findings will now be discussed in turn in relation to relevant literature.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The dancers’ ability to negotiate these transitions successfully appeared to rely on their motivation and psychological characteristics and skills ( Abbott and Collins, 2004 ; Stambulova et al, 2009 ), and, due to the exploratory and inductive nature of the research, additional factors such as social support, experience, and work-life balance. These findings provide support for a number of previous studies in areas including motivation (e.g., Aujla et al, 2014 , 2015 ), mental skills (e.g., Vealey, 2007 ) and PCDEs ( MacNamara et al, 2010a , b , 2008 ; MacNamara and Collins, 2011 ), and represent the first time that such factors have been investigated simultaneously in dance. The key findings will now be discussed in turn in relation to relevant literature.…”
Section: Discussionsupporting
confidence: 87%
“…The dancers reported a number of reasons for working independently, which included a strong love and passion for dance. Previous research has indicated that dancers are passionate about dancing, and that this passion is an important component of their commitment to dance ( Aujla et al, 2014 , 2015 ). Just like young dancers and those in training ( Alter, 1997 ; Nieminen, 1998 ; Aujla et al, 2014 ), the participants enjoyed the intrinsically motivating characteristics of dance such as creativity and working across artistic disciplines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations